2003
DOI: 10.1097/00126334-200310010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Patient Education Program on Adherence to HIV Medication

Abstract: Patients' knowledge of their HIV condition and its treatment, which has been recognized as a factor that influences adherence to antiretroviral therapy, can be improved through educational programs. This prospective, randomized, controlled trial compared an experimental group that participated in an educational program and a control group with standard care. The study evaluated the impact of an educational intervention on adherence to antiretroviral therapy, patients' knowledge, quality of life, and therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(86 citation statements)
references
References 15 publications
1
79
2
2
Order By: Relevance
“…The study by Goujard et al 6 may have not shown a change in QoL despite the increase in adherence, due to patients being asymptomatic at the beginning of the study and having high QoL. Therefore, there was little room for improvement in QoL after the intervention.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The study by Goujard et al 6 may have not shown a change in QoL despite the increase in adherence, due to patients being asymptomatic at the beginning of the study and having high QoL. Therefore, there was little room for improvement in QoL after the intervention.…”
Section: Discussionmentioning
confidence: 93%
“…One of the studies showed a worse QoL after increased adherence, 27 and the other did not show any correlation between these factors. 6 Wu et al 29 evaluated the impact on QoL of a medication reminder device for patients with HIV. The experimental group received the device, which verbally reminded the patients about the time and dosage of the medication, and in addition to this, the group received 30 minute adherence counseling sessions, monthly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings parallel the results of studies showing that educational level of nonpregnant patients with HIV and diabetes mellitus is important in the successful treatment of their disease states. [15][16][17] One possible reason for these findings is that level of educational attainment may be correlated with patient comprehension, compliance and the ability to self-manage their treatment -all of which are important factors in the treatment of complex, chronic medical conditions. Although measures of glucose control at the time of diagnosis, such as hemoglobin A1C levels, would have lent further credence to our study results, this information was not available in our data set.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Health literacy has been defined as, 'a measure of a patient's ability to read, comprehend, and act on medical instructions,' and has been shown to be of importance in the treatment of nonpregnant individuals with complex and chronic medical conditions, such as type 2 diabetes and HIV. [15][16][17] Some researchers argue that education level in itself may explain the significant differences seen in health care outcomes among patients of varying socioeconomic status. 17 As poor health literacy is clearly related to level of educational attainment, we hypothesize that education level affects the outcomes of pregnant patients with complex medical conditions, in a similar fashion as previously reported among nonpregnant individuals.…”
Section: Introductionmentioning
confidence: 99%